Hyperresponsiveness of platelets in ischemic stroke - Fateh-Moghadam, Suzanne; Htun, Patrik; Tomandl, Bernd; Sander, Dirk; Stellos, Konstantinos; Geisler, Tobias; Langer, Harald; Walton, Kodwo; Handschu, Rene; Garlichs, Christoph; Daniel, Werner G; Gawaz, Meinrad (Thrombosis and haemostasis, 2007)
Platelet activation and aggregation are critical in the pathogenesis of acute ischemic cerebrovascular diseases. The aim of our study was to characterize platelet function in patients with acute ischemic stroke or transient ischemic attack (TIA), and to evaluate the effect of platelet activation on clinical outcome. One hundred thirty-eight consecutive patients with TIA (n = 74) or stroke (n = 64) were enrolled in this study. Platelet aggregation in response to ADP, epinephrine, arachidonic acid, or collagen, and expression of platelet activation receptors (CD62P, CD63, LIBS-1 and PAC-1) in the acute phase and at three months follow-up were evaluated. Platelets derived from stroke patients were more hyperaggregable in response to agonists in the acute phase compared to TIA patients (p[ADP] = 0.002, p[arachidonic acid] = 0.047, p[epinephrine] = 0.020). Platelet activation was enhanced in the acute phase irrespective of the severity of the disease (stroke or TIA) and returned to baseline levels three months later. Persistent elevated platelet activation at three months follow-up (PAC-1) was associated with increased incidence of recurrent stroke (median, [interquartile range] 3.4, [3.0-5.2] versus 2.9, [2.3-4.0], p = 0.048). In conclusion, platelets are hyperactive in acute stroke compared with TIA. A more intensified dual antiplatelet therapy may be of benefit for stroke patients.